Si-Miao-Yong-An decoction ameliorates cardiac function through restoring the equilibrium of SOD and NOX2 in heart failure mice. (August 2019) - Ren, Yinglu; Chen, Xiangyang; Li, Peng; Zhang, Huimin; Su, Congping; Zeng, Zifan; Wu, Yan; Xie, Xuan; Wang, Qing; Han, Jing; Guo, Shuzhen; Liu, Bin; et al.
Graphical abstract: Abstract: Si-Miao-Yong-An decoction (SMYAD), a Chinese herbal formula, has been used in treating ischemic cardiovascular diseases. However, the cardioprotective mechanism of SMYAD treating heart failure (HF) remains unclear. Herein we investigated the effect of SMYAD on isoprenaline (ISO)-induced HF in C57BL/6 mice. Cardiac function and pathological changes in myocardial tissue were evaluated as well as A-type natriuretic peptide (ANP) and brain natriuretic peptide (BNP) expression. The underlying mechanism of SMYAD was deciphered using UHPLC MS/MS coupled with bioinformatics and was verified. SMYAD treatment significantly ameliorated cardiac function, reduced collagen deposition and cardiomyocyte apoptosis, reversed cardiac hypertrophy and down-regulated the expression levels of ANP and BNP mRNA compared with those in HF mice. Decipherment analyses based on 138 ingredients prompted that anti-oxidation was the key mechanism of SMYAD treating HF. In vitro and in vivo, SMYAD showed antioxidant activity, significantly up-regulated superoxide dismutase (SOD)-1 and SOD-2 mRNA expression levels and reduced NADP/NADPH ratio. Moreover, the increased expression levels of NADPH oxidase 2 (NOX2), p47 phox and Rac family small GTPase 1 (Rac1) were obviously ameliorated after SMYAD treatment. Together, this study reveals that SMYAD can apparently improve heart function of ISO-induced HF mice by inhibiting the myocardial oxidative stress through restoring the equilibrium of SOD and NOX2.